Effect of QT interval-prolonging drugs taken in pregnancy on the neonatal QT interval - Michel, Holger; Potapow, Antonia; Dechant, Markus-Johann; Brandstetter, Susanne; Wellmann, Sven; Köninger, Angela; Melter, Michael; Apfelbacher, Christian; Kabesch, Michael; Gerling, Stephan; , the KUNO-Kids study group (Frontiers in Pharmacology, 2023)
Introduction Acquired QT interval prolongations due to drug side effects can result in detrimental arrhythmia. Maternal use of placenta-permeable drugs may lead to fetal exposure and thus to an increased risk of neonatal QT prolongation and arrhythmia. Objectives To evaluate the influence of maternal QT prolonging medication on the neonatal QT interval. Methods In the prospective KUNO-Kids Health Study, an ongoing population-based birth cohort, we classified maternal medications according to known risk of QT interval prolongation. Effects on neonatal QT interval were tested in linear regression analyses, correcting for perinatal confounders (birth weight, gestational age, birth mode and age at ECG recording). Subgroup analyses were performed for selective serotonin reuptake inhibitors, proton-pump inhibitors, and the antihistamine dimenhydrinate. Logistic regression analysis was performed using a QTc of 450 ms as cut-off value. Results 2550 pregnant women received in total 3990 medications of which 315 were known for the risk of QT prolongation resulting in 105 (4.1%) neonates exposed in the last month of pregnancy. Overall, mean age of the neonates at ECG was 1.9 days and mean QTc (Bazett) was 414 ms. Univariate (regression coefficient -2.62, p=0.288) and multivariable (regression coefficient -3.55 p=0,146) regression analysis showed no significant effect of fetal medication exposure on neonatal QT interval, neither in the overall nor in the subgroup analysis. Logistic regression analysis showed no association of exposure to maternal medication with an increased risk of neonatal QT interval prolongation (OR (odds ratio) 0.34, p = 0.14). Conclusion Currently used maternal medication results in a relevant number of fetuses exposed to QT interval prolonging drugs. In our cohort, exposure was found to have no effect on neonatal QT interval.